Characterisation of the Notch receptor/ligand interaction using C. elegans as a model - Holt, L (2016)
The core aim of this project was to use the nematode worm C. elegans to probe the function of the N-terminus of Notch ligands using com- plementary molecular and in vivo approaches. Sequence analysis and structural predictions suggested that the N-termini of C. elegans Notch ligands LAG-2 and APX-1 may comprise a C2 domain, although it was concluded structural information would be necessary to confirm this. Eu- karyotic expression systems were used to produce recombinant protein fragments, and ultimately yielded a large quantity of the fragment APX- 1NE1FcHis that was purified and used for crystallography studies, although no structural information has yet been obtained from this. In parallel, assays were established to assess rescue of the mutant phenotypes associ- ated with the lag-2(q420) allele. Extrachromosomal expression of LAG-2 and APX-1 partially rescued the Lag phenotype, although overexpres- sion of ligand appeared to cause an increase in embryonic lethality. An alternative assay was established, to assess rescue of the anchor cell du- plication phenotype. Using this assay, it was demonstrated that deletion of the N-terminal MNNL or DSL domains of APX-1 abolished rescue of the phenotype observed for WT APX-1 confirming the importance of these domains in Notch signalling. Rescue was still achieved after dele- tion of the EGF-like 1 domain of APX-1, and substitutions targeting loop regions in the DSL and MNNL (DSL(ETSD), I80-K86/SS, respec- tively), but the extent of this rescue appeared to be reduced in all three constructs, suggesting these regions are required for optimised Notch signalling.